PENERAPAN ALGORITMA DECISION TREE C4.5 DALAM PENERIMAAN GURU PADA SMK SIRAJUL FALAH PARUNG - Siti Nurlela; Lestari Yusuf; Hermanto Hermanto; Elah Nurlelah; Mahmud Syarif (STIKOM CKI, 2018)
ABSTRACTSirajul Falah Vocational School is one of the private vocational high schools located in Bogor that always strives to improve quality both internally and externally on an ongoing basis in order to compete with other vocational high schools. One of the efforts made is to provide teachers who are ready to educate students of the Sirajul Falah Vocational School. However, the process of teacher acceptance in the Sirajul Falah Vocational School is still subjective. The C4.5 algorithm will be used in this study. Decision tree is a very strong and famous classification and prediction. The C4.5 algorithm is an algorithm used to form a decision tree to predict or classify a very strong one. In C4.5 algorithm to build a decision tree the thing to do is to choose an attribute as root, then create a branch for each value in the root.Keywords: C4.5 Algorithm, Data mining, Teacher acceptance.